"Entartete Kunst Lebt" at Picasso Museum Paris : March 5 - May 25 - Bartana, Yael (Picasso Museum, 2025)
We are thrilled to announce that Yael Bartana has been invited to the Musée national Picasso-Paris with the video work “Entartete Kunst Lebt” as part of the group show: “L’art dégénéré: Le procès de l’art moderne sous le nazisme”, until May 25th, 2025. Created in 2010, the animated film “Entartete Kunst Lebt” appears to bring back to life the painting Kriegskrüppel, painted by Otto Dix in 1920 and destroyed shortly after 1937. The figures in the composition—terrifying, mutilated war veterans—begin to move like creaking mechanical puppets, eventually forming a menacing crowd: the return of the repressed, the specter of a martyred painting. When the Nazis came to power in Germany, Otto Dix was immediately labeled a “degenerate” artist. Stripped of his position as a professor at the Dresden Academy, he withdrew to the shores of Lake Constance in the southwest of the country. In 1937, his iconic works, The Trench and War Cripples, were displayed in Munich as part of the Entartete Kunstexhibition, orchestrated by the Nazi regime to discredit modern art. Deemed subversive, these paintings were later burned, like so many other creations banned by the totalitarian ideology.
Keywords: Degenerate Art; Otto Dix; Picasso Museum; Paris; War